Size optimization method of the Watt-II six-bar mechanism based on particle swarm optimization - H. Ye; H. Ye; Z. Niu; Z. Niu; D. Han; D. Han; X. Su; X. Su; W. Chen; W. Chen; G. Tu; G. Tu; et al. (Mechanical Sciences)
Aiming at the difficult problem of comprehensive scale design of the six-bar mechanism in engineering practice, kinematic and dynamic analysis and modeling of the Watt-II six-bar mechanism were carried out and combined with the particle swarm optimization (PSO) algorithm, the size optimization model of the Watt-II six-bar mechanism was established, and the size optimization of the Watt-II six-bar mechanism was completed. The results show that the optimized mechanism can improve the output capacity of the mechanism and reduce the force of the parts while ensuring the motion stability, which has certain practical significance in engineering.